The burden of suspected strokes in uMgungundlovu - Can biomarkers aid prognostication? - Juan M. Jansen van Vuuren; Somasundram Pillay; Ansuya Naidoo (AOSIS, 2023)
Background: The burden of stroke is increasing worldwide. The hierarchical healthcare referral system in South Africa (SA) poses unique challenges to clinicians when caring for people with suspected strokes (PsS). To improve health outcomes, novel strategies are required to provide adequate care, including prognostication, in SA. Aim: To determine the subjective burden of and challenges posed by suspected stroke cases and the potential usefulness of biomarkers in prognostication. Setting: This study was conducted in the uMgungundlovu Health District (UHD), KwaZulu-Natal, SA. Methods: An online questionnaire was distributed to doctors within the UHD. Demographic data and answers to a series of 5-point-Likert-type statements were collected. Results: Seventy-seven responses were analysed. A third of doctors worked in primary healthcare facilities (PHCare) and saw ≥ 2.15 suspected strokes-per-doctor-per-week, compared to ≥ 1.38 seen by doctors working in higher levels of healthcare. Neuroimaging was relied upon by 85% of doctors, with nearly half of PHCare doctors having to refer patients to facilities 5 km - 20 km away, with resultant delays. Knowledge about prognostic biomarkers in strokes was poor, yet most doctors believed that a biomarker would assist in the prognostication process and they would use it routinely. Conclusion: Doctors in this study faced a significant burden of strokes and rely on neuroimaging to guide their management; however, many challenges exist in obtaining such imaging, especially in the PHCare setting. The need for prognostic biomarkers was clear. Contribution: This research lays the platform for further studies to investigate prognostic biomarkers in stroke in our clinical setting.